2010
DOI: 10.1371/journal.pcbi.1000999
|View full text |Cite
|
Sign up to set email alerts
|

On the Inverse Problem of Binocular 3D Motion Perception

Abstract: It is shown that existing processing schemes of 3D motion perception such as interocular velocity difference, changing disparity over time, as well as joint encoding of motion and disparity, do not offer a general solution to the inverse optics problem of local binocular 3D motion. Instead we suggest that local velocity constraints in combination with binocular disparity and other depth cues provide a more flexible framework for the solution of the inverse problem. In the context of the aperture problem we der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…The same projective geometry that defines monocular optic flow information (Gibson 1950) also gives rise to the differing monocular signals for velocity- and disparity-based binocular computations—a simple by-product of the two eyes being horizontally offset but otherwise following the same fundamental geometry. The importance of integrating binocular and monocular cues to 3D motion has been proposed as a crucial component to solving the inverse 3D-motion-correspondence problem (Lages & Heron 2010) and is an important component of recognizing the full geometric dependencies inherent to binocular visual perception.…”
Section: Binocular Cues For the Perception Of 3d Motionmentioning
confidence: 99%
“…The same projective geometry that defines monocular optic flow information (Gibson 1950) also gives rise to the differing monocular signals for velocity- and disparity-based binocular computations—a simple by-product of the two eyes being horizontally offset but otherwise following the same fundamental geometry. The importance of integrating binocular and monocular cues to 3D motion has been proposed as a crucial component to solving the inverse 3D-motion-correspondence problem (Lages & Heron 2010) and is an important component of recognizing the full geometric dependencies inherent to binocular visual perception.…”
Section: Binocular Cues For the Perception Of 3d Motionmentioning
confidence: 99%
“…Although these two models imply vastly different neural architectures (IOVD is based on motion-selective cells, while CDOT is based on disparity-selective cells), most current studies have shown that both IOVD and CDOT support the perception of MID (Nefs et al 2010;Rokers et al 2009). It should be noted that neither IOVD nor CDOT cues alone are sufficient for defining 3D motion trajectories in a general fashion (Lages and Heron 2010).…”
mentioning
confidence: 99%
“…The present approach extends existing probabilistic models [24,11] to 3D motion and provides a velocity estimate for the 3D aperture problem [12]. The underlying geometricstatistical model is based on monocular constraints in a binocular viewing geometry.…”
Section: Bayesian Models Of 3d Motion Perceptionmentioning
confidence: 98%
“…Adjustments of the depth probe was used to establish perceived motion direction in terms of azimuth and elevation angle from the start point in the centre of the aperture. It was tested whether perceived motion direction of oblique stimulus lines were systematically affected by orientation disparity [12].…”
Section: Experiments 1: Perceived Motion Direction Of Oblique Linementioning
confidence: 99%
See 1 more Smart Citation